2016
DOI: 10.1111/gcbb.12402
|View full text |Cite
|
Sign up to set email alerts
|

Biochar stimulates the decomposition of simple organic matter and suppresses the decomposition of complex organic matter in a sandy loam soil

Abstract: Incorporating crop residues and biochar has received increasing attention as tools to mitigate atmospheric carbon dioxide (CO 2 ) emissions and promote soil carbon (C) sequestration. However, direct comparisons between biochar, torrefied biomass, and straw on both labile and recalcitrant soil organic matter (SOM) remain poorly understood. In this study, we explored the impact of biochars produced at different temperatures and torrefied biomass on the simple C substrates (glucose, amino acids), plant residues (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…Specifically, biochar has been shown to cause selective positive priming of simple soil organic matter molecules and fresh plant residues (Arif et al, 2016; Cui et al, 2017; Farrell et al, 2015). Our findings of an apparent positive priming in response to bicarbonate‐soluble biochar OC amendment are in agreement with assertions that biochar LOC is largely responsible for observed positive priming effects of biochar (Cheng et al, 2016; Cross and Sohi, 2011). For the biochars studied here, positive priming with untreated biochar amendment was likely prevented by sorption of the biochar LOC pool to the solid biochar matrix that occurred when acid‐ or base‐extracted biochar LOC was added to soils separately.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, biochar has been shown to cause selective positive priming of simple soil organic matter molecules and fresh plant residues (Arif et al, 2016; Cui et al, 2017; Farrell et al, 2015). Our findings of an apparent positive priming in response to bicarbonate‐soluble biochar OC amendment are in agreement with assertions that biochar LOC is largely responsible for observed positive priming effects of biochar (Cheng et al, 2016; Cross and Sohi, 2011). For the biochars studied here, positive priming with untreated biochar amendment was likely prevented by sorption of the biochar LOC pool to the solid biochar matrix that occurred when acid‐ or base‐extracted biochar LOC was added to soils separately.…”
Section: Discussionsupporting
confidence: 92%
“…Considering longevity of charcoal in soils and its capability to sorb non‐pyrolyzed organic matter, several authors ( Borchard et al, ; Cheng et al, ; Hardy et al, ; Kerré et al., ) concluded that the presence of charcoal in soils most likely affects quantity and quality of dissolvable organic matter. In the present study, the presence of charcoal in soils of abandoned kiln sites reduced the total amount of WEOC relative to the corresponding reference soils, as also reported by Kerré et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Lignin‐like compounds found in all samples indicate the ubiquitous presence of transitional forms of plant biomass and lignin‐like compounds released from charcoal that are enriched and formed during SOM stabilization processes ( Blume et al, ; Ohno et al, ; Lu et al, ). However, the less‐evident presence of condensed hydrocarbon signals in the water extracts of charcoal enriched soils may indicate a sorption of highly aromatic humified fragments onto charcoal particles (both are poorly water‐soluble) and thus stabilization of complex organic molecules by charcoal ( Cheng et al, ). However, varying abundances of condensed hydrocarbons with less abundance in topsoil than in subsoil may indicate their decomposition in topsoil or their translocation into subsoil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations